Bassetki Statue with an Old Akkadian Royal Inscription of Narām-Sin of Agade (B.C. 2291-2255) - Ayish, Abdul-Hadi
ersch. 1977; IM 77823, cast metal life-size statue found at Bassetki near Mosul; cf. (in Arabic) Tariq Madhloom, Studies in the Akkadian Bronze Statue: ibid. 41-48, 16 pl.; Fawzi Reschid, Preliminary Studies on the Bassetki Statue: ibid. 49-58, 2 pl.